2016
DOI: 10.1530/joe-15-0518
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor (AR) in cardiovascular diseases

Abstract: Cardiovascular diseases (CVDs) are still the highest leading cause of death worldwide. Several risk factors have been linked to CVDs, including smoking, diabetes, hyperlipidemia, and gender among others. Sex hormones, especially the androgen and its receptor, androgen receptor (AR), have been linked to many diseases with a clear gender difference. Here, we summarize androgen/AR effects on CVDs, including hypertension, stroke, atherosclerosis, abdominal aortic aneurysm (AAA), myocardial hypertrophy, and heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 188 publications
(211 reference statements)
0
72
0
1
Order By: Relevance
“…24 Studies have shown that testosterone receptors in cardiomyocytes can induce the release of intracellular calcium in cardiomyocytes and, as a result, testosterone deficiency can lower the contractile function of the myocardium. 2527 Our findings may be due to interruption of the cardiometabolic and vascular derangement that is hypothesized to occur with intermittent but not with continuous administration of ADT.…”
Section: Discussionmentioning
confidence: 81%
“…24 Studies have shown that testosterone receptors in cardiomyocytes can induce the release of intracellular calcium in cardiomyocytes and, as a result, testosterone deficiency can lower the contractile function of the myocardium. 2527 Our findings may be due to interruption of the cardiometabolic and vascular derangement that is hypothesized to occur with intermittent but not with continuous administration of ADT.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, androgenic anabolic steroids are commonly administered with other drugs such as β 2 ‐mimetics, illicit sympathomimetics, diuretics, and/or psychoactive drugs . Data on testosterone's effects on the cardiovascular system are mixed and they differ from those elicited by supraphysiologic doses of synthetic androgens . Thus, it is not easy to decipher the cardiovascular impact of anabolic androgenic steroid abuse.…”
Section: Drugs With Possible Toxic Effects On Both Cardiomyocytes Andmentioning
confidence: 78%
“…Indeed, cardiac pathology is commonly observed in young people who died while abusing androgens . Other effects of anabolic androgenic steroid abuse include a small increase in arterial blood pressure, which is expected due to the known physiological difference between men and women . The cause can be increased sodium and water retention, or effects on red blood cell proliferation through increased expression of erythropoietin.…”
Section: Drugs With Possible Toxic Effects On Both Cardiomyocytes Andmentioning
confidence: 99%
See 2 more Smart Citations